Enhanced Electrochemical Properties of Catalyst by Phosphorous Addition for Direct Urea Fuel Cell - Lee, Unho; Lee, You Na; Yoon, Young Soo (Frontiers in Chemistry, 2020)
An anode bimetallic catalyst comprising Ni-Pd alloy nanoparticles was loaded on acid-treated multi-walled carbon nanotubes (MWCNTs) for application in a direct urea fuel cell. The bimetallic catalyst and MWCNTs were synthesized by a hydrothermal method at 160℃ for 5 h. To reduce the catalyst particle size, alkaline resistance, and facilitate their uniform distribution on the surface of the MWCNTs, phosphorus (P) was added to the Ni-Pd/MWCNT catalyst. The effects of P on the distribution and reduction in size of catalyst particles were investigated by Brunauer–Emmett–Teller analysis, transmission electron microscopy, and X-ray diffraction analysis. The enhanced catalytic activity and durability of the P-containing catalyst was confirmed by the high current density (1897.76 mA/cm2 (vs. Ag/AgCl)) obtained at 0.45 V in a 3 M KOH/1.0 M urea alkaline aqueous solution compared with that of the catalyst without P (604.87 mA/cm2 (vs. Ag/AgCl)), as determined by cyclic voltammetry and chronoamperometry. A urea–air fuel cell assembled with a membrane electrode assembly comprising the Ni-Pd(P)/MWCNT catalyst delivered peak power densities of 0.756 and 3.825 mW/cm2 at 25℃ and 60℃, respectively, in a 3 M KOH/1 M urea solution.